Effect of sperm pretreatment with glutathione and membrane destabilizing agents lysolecithin and Triton X‐100, on the efficiency of bovine intracytoplasmic sperm injection. (6th January 2017) - Zambrano, F; Aguila, L; Arias, ME; Sanchez, R; Felmer, R
Contents: Intracytoplasmic sperm injection (ICSI) is an assisted reproduction tool with several applications. Its effectiveness in bovines is lower than that in other species, mainly because of difficulties in the decondensation of the sperm nucleus after injection, and the presence of the acrosome and the plasma membrane which remain intact in this procedure. In this study, we assessed the effect of lysolecithin (LL) and Triton X‐100 (TX), in combination with glutathione (GSH) as sperm pretreatments prior to ICSI. The GSH‐LL and GSH‐TX groups showed 0% of spermatozoa with intact membrane (SYBR 14+/PI), in comparison with the control (63.3%) and GSH (65.7%) groups. The proportions of spermatozoa with damaged acrosome membrane in the GSH‐LL, GSH‐TX, GSH and control groups were 46%, 35.9%, 10.5% and 7.5%, respectively. Sperm chromatin decondensation analysis showed that the groups incubated for 3 hr with GSH presented greater decondensation ( p < .05). Although fertilization was improved in all treatment groups evaluated, no differences were observed in the cleavage rate 72 hr after activation in the GSH (73.7%), GSH‐LL (80.2%) and GSH‐TX (77.8%) groups compared to the control (66.3%), neither in the blastocyst rate on day 8 (24.0%, 26.2%, 27.1% and 28.4% for the control, GSH, GSH‐LL and GSH‐TX groups, respectively). No differences were also observed in the total number of cells in all groups. In conclusion, although these sperm treatments promoted nuclear decondensation and induced plasma membrane disruption, these effects were not sufficient to improve bovine embryonic development after ICSI.